CORONAVIRUS PANDEMIC AND INTERNALLY DISPLACED PERSONS IN AFRICA - IGBOKE, Shedrack C; OGONNA, Paul Samuel (Socialscientia: Journal of Social Sciences and Humanities, 2021)
This paper interrogates the novel Coronavirus pandemic and how it affects internally displaced persons in Sub-Saharan Africa. It states that the internally displaced have over the years endured an awful abandonment by the UN, humanitarian organizations and national governments as well until lately towards the period of the end of the cold war when due attention began to the given to internal displacements like the refugees are. The paper underscores the fact that various factors are responsible for the state of the IDPs, however, prominent among these factors is the issue of sovereignty of states. Nations tend to protect their territorial spaces from all forms of external interventions, and this situation the UN and other humanitarian agencies are aware of. This paper uses the systems theory to interrogate the fact that the deliberate or oblivious negligence of the plights of the internally displaced remains a cog in the machine of progress in international relations and the battle to flatten the curve of the spread of the Covid 19 pandemic. The qualitative method of data analysis shall be adopted to ensure an objective interrogation of these concepts, hence primary and secondary source materials shall be used. It concludes that until the internally displaced are given a due attention just like their counterparts; the refugees, since they are also bona fide citizens of their home states and also a unit of the globe, it continues to be a spot on international relations and the international fight against Covid 19. The paper recommends that international organizations, national governments and non-governmental organizations should give due attention to the internally displaced like it is being given to refugees.